2005
DOI: 10.1016/s1322-7696(08)60480-1
|View full text |Cite
|
Sign up to set email alerts
|

Medication errors and professional practice of registered nurses

Abstract: This Australian study identified and described the incidence of medication errors among registered nurses, the type and causes of these errors and the impact that administration of medications has on the professional practice of registered nurses. Mostly, medication errors were attributed to documentation issues, including: illegible handwriting, misunderstanding abbreviations, misplaced decimal point, misreading and misinterpreting written orders. Several human factors were attributed to potential causes of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
83
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(86 citation statements)
references
References 15 publications
0
83
0
3
Order By: Relevance
“…This is supported by Nichols et al (2008) who report that more than two thirds of doctors describe poor communication during hand over of care, combined with insufficient guidance from more senior colleagues as contributing to medication error. In the same study, nurses also reported that poor communication within the nursing team contributed to error, while Deans (2005) found that written communication was a significant contributing factor. In particular, misreading, misinterpreting, or illegible handwriting could account for nearly one fifth of errors (Deans, 2005).…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…This is supported by Nichols et al (2008) who report that more than two thirds of doctors describe poor communication during hand over of care, combined with insufficient guidance from more senior colleagues as contributing to medication error. In the same study, nurses also reported that poor communication within the nursing team contributed to error, while Deans (2005) found that written communication was a significant contributing factor. In particular, misreading, misinterpreting, or illegible handwriting could account for nearly one fifth of errors (Deans, 2005).…”
Section: Discussionmentioning
confidence: 88%
“…In the same study, nurses also reported that poor communication within the nursing team contributed to error, while Deans (2005) found that written communication was a significant contributing factor. In particular, misreading, misinterpreting, or illegible handwriting could account for nearly one fifth of errors (Deans, 2005). This would suggest that an increased awareness of the importance of accurate and unambiguous communication can improve medication safety.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations